Regulations in the Economy and the Change of the Real Structure of the Economy under Conditions of Systemic Transformation - Piotr WALĄG (Communications of International Proceedings, 2020)
The economies of transforming Central and Eastern Europe, as countries burdened with multiple barriers, which are the remnants of the socialist economic system, are included as an area of research into the possible impact of regulation on the directions and pace of change in employment and production structures. It is often possible to point out certain significant similarities between the changes taking place in these countries and those taking place in countries that are advanced in the development of a market economy. Changes in economic structures are the result of numerous, varied and separate processes. The legacy of the planning economic system is the backwardness associated with the development of the services sector, which has made up for its development significantly in response to the needs of developing business in the country and the freedoms carried by law for private enterprises. Deregulation has been widely undertaken, often as part of a structural adjustment programme, mainly with the aim of relieving market economy mechanisms of their regulatory constraints and making fuller use of their developmental potential. The scale of the impact of regulation on economic growth was strongly determined by the regulation of key sectors of the economy. The aim of the article is, on the basis of the analysis of key economic measures, to indicate and determine the possible relationship between the regulatory burden, generally understood as state control, restrictions on entrepreneurship, free trade and investment, and the shape of the structure of selected CEE economies.
Keywords: real structure of the economy; deindustrialisation; reindustrialisation; deregulation; regulation; systemic transformation; economic governance; market competition.